Analysis of Temporal Speech Impairments in Prodromal Dementia with Lewy Bodies - Davaajargal, Anar; Novotny, Krystof (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2025)
Dementia with Lewy bodies (DLB) is the second most common form of neurodegenerative dementia. The progressive deterioration of motor and cognitive functions, accompanied by behavioral changes, severely impacts the quality of life of affected individuals and those around them. Early diagnosis is therefore essential for timely intervention and appropriate treatment. Despite its possible clinical significance, research specifically addressing speech impairments in DLB remains limited. Acoustic analysis offers a cost-effective, non-invasive approach for paraclinical diagnosis, yet its potential in identifying DLB-specific speech patterns remains partially underexplored. This study investigates a key aspect of speech production—temporal parameters (related to speech tempo and pauses), with an extension into the linguistic domain. Statistical evaluation was conducted using the Mann-Whitney U test and descriptive analysis. Notable discriminatory power in differentiating the prodromal DLB group from healthy controls was observed for parameters such as MWPM of Longer Words, Median Pause Length, Occurrence of Repeated Words, and Net Speech Rate, particularly in the monologue task, which exhibited greater effectiveness compared to the text-reading task. This analysis underscores the potential utility of temporal speech parameters for the early detection of DLB while also introducing and evaluating novel custom metrics tailored for this purpose.
Keywords: acoustic analysis; dementia with Lewy bodies; temporal speech parameters; digital speech biomarkers